Enabling sustainable diets into elementary education: Participatory action research - Yayuk Farida Baliwati; Akifa Laila Rusyda; Cesilia Meti Dwiriani; Siti Amanah; Resa Ana Dina; Prita Dhyani Swamilaksita; Jihan Alfira; Veny Rachmalinda (Journal of Community Service and Empowerment, 2025)
School-based nutritional education is a promising intervention in overcoming public health nutritional problems with desirable results through behavioral changes. The present study aims to analyze nutritional contents or topics on Pancasila Student Profile (Independence Curriculum) on the sustainable diet promotion in elementary school settings. The design of the present study was a qualitative Participatory Action Research (PAR), recruited purposively 30 elementary teachers. The study was conducted at SD Plus Rahmat, Kediri, Indonesia from June to July 2024. The nutritional education consisted of three sessions, including introduction, project-based module development (learning plans), and module presentation and discussion. Result shows that the sustainable diets topic has been integrated on the P5 learning activity theme through ‘Sustainable Lifestyle” in phase A, B, and C among all classes. The topics of sustainable diets on the previous curriculum and lesson plans were performed using content analysis. The content analysis maps the previous topics related to the sustainable diets in the P5 module which has been developed by school. The result shows that learning hours for nutritional education at the elementary class settings was estimated around 68 – 110 learning hours in a year. The learning activity was arranged following four types of activity, including introduction, contextualization, action, and reflection.